HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP IBU TENTANG GIZI SEIMBANG DENGAN PERKEMBANGAN BAYI USIA 6-12 BULAN DIWILAYAH KERJA PUSKESMAS LUBUK ALUNG TAHUN 2022 - Eliza Eliza; Septa Nelli (Ensiklopedia Education Review, 2022)
Problems in infantdevelopment can occur especially in the first years of life, so it is necessary to have early detection of deviations in infant development so that appropriate prevention and intervention efforts can be made Early detection can be carried out by professional cadres, families, especially mothers as the closest people. (Utami, 2016) The purpose of the study was to determine the relationship between the level of knowledge and mother’s attitude about balanced nutrition with the development of infants aged 6-12 months in the working area of the Lubuk Alung Health Center.The scope of this study was to determine the relationship between the level of knowledge and mother’s attitude about balanced nutrition with the development of infants agend 6-12 months in the working area of the Lubuk Alung Health Center..the independent variable is the development of infants aged 6-12 months. The research method uses quantitative descriptive with a cross sectional study design. This research was carried out in September 2022 in the Lubuk Alung Health Center Work Area. The population of this study was the parents of 115 babies with a total sample of 54 people. Analysis of the results of the study was carried out univariate and bivariate or computerized.The results showed that more than half of 24 (44,4%) respondents had a moderate level of knowledge, half of 29 (53,7%) respondents had a negative attitude, more than half of 30 (55,6%) respondents had stimulation of infant motor developmentabnormal, there is a significant relationship between the level of knowledge and the provision of stimulation for infant motor development, there is a significant relationship between attitudes and the provision of stimulation for infant motor development in the Lubuk Alung Health Center Working Area in 2022.The results of the research are expected that health workers can intensify their outreach to mothers during posyandu and when mothers make visits to puskesmas.